INFLUENCE OF ESTABLISHMENT METHODS AND NITROGEN LEVELS ON YIELD ATTRIBUTES, YIELD, NUTRIENTS UPTAKE AND ECONOMICS OF KHARIF RICE IN INCEPTISOLS OF WARANGAL DISTRICT - CH.RAMULU*, E.NARSAIAH and P. RAGHU RAMI REDDY (The Journal of Research ANGRAU, 2020)
The field experiment was conducted during Kharif 2015, 2016 and 2017 at Regional Agricultural ResearchStation, Warangal to study the effect of establishment methods (machine transplanting, conventionaltransplanting, drum seeding and broad casting) and nitrogen levels (120 kg ha-1,160 kg ha-1 and 200 kg ha-1) ina strip plot design. Number of panicles m-2, grains panicle-1, grain and straw yields (317 kg ha-1, 277 kg ha-1,5345 kg ha-1 and 6305 kg ha-1, respectively) were significantly high under machine transplanting over otherestablishment methods.Significantly higher number of panicles m-2, grains panicle-1, grain and straw yields(263 kg ha-1, 276 kg ha-1, 4838 kg ha-1 and 6109 kg ha-1, respectively) were recorded with the application of 160kg N ha-1 over 120 kg N ha-1 but at par with 200 kg N ha-1.The interaction effect between establishment methodsand nitrogen levels was non-significant during all the years of study. The net income (Rs.64,587/-) as well asreturn per rupee invested (1:3.1) was maximum with machine transplanting followed by broadcasting (1:3.0).